The effects of a human patient simulator vs. a CD-ROM on performance. - Johnson D; Corrigan T; Gulickson G; Holshouser E; Johnson S; Johnson, Don; Corrigan, Theresa; Gulickson, Gary; Holshouser, Elizabeth; Johnson, Sabine (Military Medicine, 2012)
Objectives: Military health care personnel need to have skills relative to caring for patients on the battlefield. No studies have compared the two teaching strategies of using the human patient simulator (HPS) and a CD-ROM in caring for combat injuries. The objective of this study was to determine if there were statistically significant differences in HPS and CD-ROM educational strategies relative to caring for patients who have trauma.Methods: A pretest/post-test prospective experimental design was used. Anesthesia students were randomly assigned to one of three groups: HPS, CD-ROM, or a control group. A valid and reliable instrument, Combat Performance, was used to evaluate the participant's ability to give care to trauma patients.Results: A repeated analysis of variance and a least significant difference post hoc test were used to analyze the data. The HPS group performed better than the CD-ROM and control groups relative to performance (p = 0.001). There was no difference between the CD-ROM and control group (p = 0.171).Discussion: We speculate that the HPS group performed better than the CD-ROM group because of the realism.Conclusion: In this study, the HPS method of instruction was a more effective method of teaching than the CD-ROM approach.